PO-18 - Fibronectin EDA/EDB is expressed in adherent SCLC NCI-H69 cells and in pleural effusions of lung cancer patients: possible implication for drug resistance. Issue 140 (April 2016) - Salge-Bartels, U.; Heiden, M.; Seitz, R.; Gieseler, F.
Abstract : Introduction: Small cell lung cancer (SCLC) is an extremely aggressive tumour which metastasizes early. Even if chemotherapy can achieve an initial regression, relapses due to chemo-resistance are almost inevitable. Sethi et al (Nat Med. 1999;5:662-668) reported that matrix proteins are essentially involved in the development of drug resistance. SCLC cells in suspension culture secrete negligible amounts of matrix proteins Aim: For a more detailed study of the SCLC ability to produce matrix proteins we applied a recently introduced cell culture model of adherence selected SCLC (Salge et al. J Cancer Res Clin Oncol. 2001;127(2):139-411) and analysed pleural effusions form lung cancer patients. Materials and Methods: Adherent cells were selected from the SCLC cell line NCI-H69 after exposure to cellular stress. Pleural effusion were obtained from lung cancer patients (SCLC and NSCLC) and from pleural effusions (PE) with congestive heart failure Protein expression was analysed by western blotting (WB) and flow cytometry using specific antibodies against the fibronectin extra domain A (FnEDA) and B (FnEDB) (Sirius, Italy), and for integrins alpha 1-5 and beta 1-3. Drug resistance was assessed with the metabolic stain MTT (3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium-bromid). Results: SCLC suspension cells expressed negligible amounts of fibronectin. In contrast, adherent H69 cells, which showed a significantly reduced chemo-sensitivity against carboplatin and doxorubicin, strongly expressed FnEDA and to a lesser extent FnEDB. Furthermore, in adherent cells expression of various integrins was up-regulated, in particular integrins alpha5/beta3, representing potential binding sites for FnEDA/FnEDB. Analysis of pleural effusions clearly showed the presence of FnEDA/ FnEDB in those of lung cancer patients, whereas in benign pleural effusion almost no FnEDA/ FnEDB was found. Conclusions: Our data reveal the presence of Fn, and its splice variants FnEDA/EDB in particular, in adherent SCLC cells as well as in malignant PE. We assume that the splice variants FnEDA/ FnEDB are linked to cancer progression and chemo-resistance in this tumour type.